Respon Pertumbuhan dan Hasil Pakcoy (Brassica campestris var. chinensis) Hidroponik pada Pemberian Konsentrasi Pupuk NPK dan Pupuk Daun - Maudi Sugesti Junior; Rizka Novi Sesanti; Desi Maulida; Sismanto Sismanto; Fahri Ali; Yeni Yeni (Journal of Horticulture Production Technology, 2023)
Hydroponic crop cultivation generally uses AB mix nutrient. However, the expensive price of AB Mix nutrient caused increasing production costs. In addition to the expensive price, the availability of AB Mix is also limited. As an alternative, there is a need for more affordable fertilizer such as compound fertilizer and foliar fertilizer. The purpose of this study was to (1) determine the best compound fertilizer concentration to growth and yield of Pakcoy; (2) determine the best foliar fertilizer concentration to growth and yield of Pakcoy; (3) determine the interaction between compound and foliar fertilizer to growth and yield of Pakcoy. This study was used Split Plot Randomized Block Design consist 2 replicated. Main plot was compound fertilizer concentration and sub plot was foliar fertilizer concentration.The resulted of this study was (1) 2.5 g/L compound fertilizer concentration provide the best growth and yield of Pakcoy; (2) there was no significant effect of foliar fertilizer concentration; (3) there was no interaction between tho treatnments.